Peran Perpustakaan Baitul Hikmah pada Masa Bani Abbasiyah - muthakin muthakin (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
In the Abbasid period, Baitul Hikmah became the main resource center for the scholar or researcher in the Baghdad city. The Baitul Hikmah or well-known as a house of wisdom, was developed since the the second caliph administration led by Abu Ja’far al-Manshur (754-775 A.D.). Abu Ja’far al-Manshur was known as a caliph who attracted profoundly to science. By his regulation, he pioneered the translation of scientific and literature from foreign languages. Large number of books from India, Ancient Greek, Bizantine, Persian and Syria were translated into Arabic. This tradition was followed by his succesor, the caliph of Harun ar-Rasyid (786-809 A.D.) and his descendant, the caliph of Al-Ma’mun (813-833 A.D.). In the Al-Ma’mun era, Baitul Hikmah witnessed an overwhelming enhancement. As a result, Baitul Hikmah was not only becoming a house of numerous books, but also as a center of translation, research and publication, the study of astrology, and educational institutions in general.